The Librarian in the Complexity of the Labor Market in the Digital Economy - Cintra Fermann, Angélica; Paletta, Francisco Carlos (Cadernos de Educação Tecnologia e Sociedade, 2022)
This article presents reflections on research in progress, which seeks to understand the profession of information professionals, based on their training, technical and behavioral skills in the digital economy, dictated by emerging technologies. The purpose is to provide new reflections on the challenges imposed by the labor market on librarians, whose skills are not exclusive to their training and can be incorporated by many other professions. The use of the Quadripolar methodology supported by the Delphi technique allows understanding a context that is still being built on a future scenario, the librarian's career in a network economy. The research pillars are training and employability. There are composed by scholars, recruiters or recruitment companies and companies that are undergoing digital transformation or were born digital. The research is document based on the vision of labor and its dimensions and careers; moving on to the digital era where the choice of professional, their skills and abilities becomes a strategy in the adopted business model. In this framework, information preferably dialogues with digital technologies and the future of work, which has been widely debated by organizations around the world.